2000
DOI: 10.1161/01.cir.101.23.2749
|View full text |Cite
|
Sign up to set email alerts
|

Na + /H + Exchange Inhibition With HOE642 Improves Postischemic Recovery due to Attenuation of Ca 2+ Overload and Prolonged Acidosis on Reperfusion

Abstract: Background —Na + /H + exchange inhibition with HOE642 (cariporide) improves postischemic recovery of cardiac function, but the mechanisms of action remain speculative. Because Na + /H + exchange is activated on reperfusion, it was hypothesized that its inhibition delays realkalinization and decreases intracellular Na + and, via Na + /Ca 2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 38 publications
3
79
0
3
Order By: Relevance
“…This could be achieved by inhibiting I NHE or late I Na . Both approaches were cardioprotective in experimental models of ischemia/ reperfusion, since in this situation, an excessive increase of [Na + ] i contributes to progressive cytosolic and mitochondrial Ca 2+ -overload and thus, the induction of apoptosis through activation of the mitochondrial PTP [78,135,168,189]. Also in animal models of heart failure, both the inhibition of I NHE by cariporide and of late I Na by ranolazine reduced [Na + ] i and improved EC coupling and LV remodeling [6,34,38,62,163,202].…”
Section: Discussionmentioning
confidence: 99%
“…This could be achieved by inhibiting I NHE or late I Na . Both approaches were cardioprotective in experimental models of ischemia/ reperfusion, since in this situation, an excessive increase of [Na + ] i contributes to progressive cytosolic and mitochondrial Ca 2+ -overload and thus, the induction of apoptosis through activation of the mitochondrial PTP [78,135,168,189]. Also in animal models of heart failure, both the inhibition of I NHE by cariporide and of late I Na by ranolazine reduced [Na + ] i and improved EC coupling and LV remodeling [6,34,38,62,163,202].…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report on measurements of Ca 2ϩ transients with aequorin in perfused mouse hearts at 37°C, and the protocol is therefore described in detail. After an initial perfusion period of 5-10 min at 30°C with a Ca 2ϩ concentration ([Ca 2ϩ ]) in the coronary perfusate of 1.0 mM, aequorin was macroinjected with a technique adapted from the rat whole heart preparation (22) and modified for the intact mouse heart. Specifically, 3-5 l of an aequorin-containing solution (1 g/ml) were injected with a glass micropipette into the interstitium of the inferoapical region of the LV.…”
Section: Animalsmentioning
confidence: 99%
“…8,9 Activation of this exchanger in myocardial ischemia appears to be causally related to the calcium overload observed during ischemia, 10 and several studies have demonstrated protection from ischemic injury by NHE inhibition both in animal models of myocardial ischemia (MI) and in patients undergoing coronary interventions. [11][12][13] A protective effect of cariporide has recently been demonstrated in the setting of post-MI remodeling, 14 where protection could be demonstrated up to 3 months after MI.…”
Section: The Cardiac Namentioning
confidence: 99%
“…20 This increased intracellular sodium might be exchanged against calcium via the cardiac Na ϩ -Ca 2ϩ exchanger, as has been proposed for the NHE1 activation observed during myocardial ischemia. 12 The resulting increase in diastolic calcium might then exert numerous deleterious effects, including the activation of protein kinase C and calcium-dependent transcription factors. Interestingly, we have found alterations in intracellular calcium handling in ␤ 1 -adrenergic receptor transgenic mice that are similar to human heart failure and include markedly prolonged calcium transients.…”
Section: Engelhardt Et Al Nhe Inhibition In ␤ 1 -Receptor Transgenic mentioning
confidence: 99%